2020
DOI: 10.1186/s41016-020-00212-2
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of using a prophylactic epidural closed drain and non-watertight dura suture in a craniotomy near the “parietal site”

Abstract: Background In neurosurgery, the necessity of having a drainage tube is controversial. Subgaleal fluid collection (SFC) often occurs, especially in a craniotomy near the “parietal site”. This study aimed to reassess the benefit of using a prophylactic epidural drainage (ED) and non-watertight dura suture in a craniotomy near the parietal site. Methods A retrospective review was conducted on 63 consecutive patients who underwent a craniotomy near the parietal site. The patients were divided into two groups acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…On multivariate analysis, we found that a watertight dura closure significantly reduced the occurrence of SFC 14 times (p = 0.015 14.15 [1.67–119.92]) and incomplete dura closure profoundly increased the likelihood of SFC and drainage use (p = 0.001 73 [5.64–959.80]). This was in disagreement with Li et al 28 who showed that among 63 patients who underwent craniotomy near the parietal site, there was significantly reduced SFC, infection, and control epilepsy with the prophylactic use of drainages and a non-watertight dura suture, findings contrary to Hamou et al 26 However, our findings were contrary to a study by Hamou and group in which they reported that despite watertight dural closure in patients who underwent supratentorial craniotomies there was no difference in the occurance rate of SFC.…”
Section: Discussioncontrasting
confidence: 82%
“…On multivariate analysis, we found that a watertight dura closure significantly reduced the occurrence of SFC 14 times (p = 0.015 14.15 [1.67–119.92]) and incomplete dura closure profoundly increased the likelihood of SFC and drainage use (p = 0.001 73 [5.64–959.80]). This was in disagreement with Li et al 28 who showed that among 63 patients who underwent craniotomy near the parietal site, there was significantly reduced SFC, infection, and control epilepsy with the prophylactic use of drainages and a non-watertight dura suture, findings contrary to Hamou et al 26 However, our findings were contrary to a study by Hamou and group in which they reported that despite watertight dural closure in patients who underwent supratentorial craniotomies there was no difference in the occurance rate of SFC.…”
Section: Discussioncontrasting
confidence: 82%
“…We believe that similar results could also be observed if a subgaleal drain had been used in the control group. Subgaleal drainage is also a less invasive and more practical method than epidural drainage (10).…”
Section: Discussionmentioning
confidence: 99%